2012
DOI: 10.1177/0265532212459028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L1 definitions and cognate status of test items on the Vocabulary Size Test

Abstract: This study examines the development and evaluation of a bilingual Vocabulary Size Test (VST, Nation, 2006). A bilingual (English–Russian) test was developed and administered to 121 intermediate proficiency EFL learners (native speakers of Russian), alongside the original monolingual (English-only) version of the test. A comparison of the bilingual and monolingual test scores showed that participants achieved significantly higher scores on the bilingual version of the test. Accuracy of responses to individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 39 publications
11
78
1
Order By: Relevance
“…We would add here that this particular pattern should not necessarily be expected across L1-L2 pairings; for instance, it would be reasonable to expect that the cognate facilitation effect should remain consistently large (or at least start to diminish at considerably lower frequencies) for speakers of Romance languages due to the fact that numerous low-frequency words in English are cognate with basic high-frequency Romance words (e.g., the low-frequency learned English word infirm is cognate with the basic Spanish term for "sick", enfermo). Elgort (2013) estimates that in her study the presence of cognates resulted in an overestimate of her participants' vocabulary size of approximately 1,000 word families. She argues, however, that cognates should still not be excluded from L2 vocabulary tests because their presence is crucial for obtaining an accurate estimate of vocabulary size.…”
Section: Cognates and Cognate Facilitationmentioning
confidence: 96%
See 1 more Smart Citation
“…We would add here that this particular pattern should not necessarily be expected across L1-L2 pairings; for instance, it would be reasonable to expect that the cognate facilitation effect should remain consistently large (or at least start to diminish at considerably lower frequencies) for speakers of Romance languages due to the fact that numerous low-frequency words in English are cognate with basic high-frequency Romance words (e.g., the low-frequency learned English word infirm is cognate with the basic Spanish term for "sick", enfermo). Elgort (2013) estimates that in her study the presence of cognates resulted in an overestimate of her participants' vocabulary size of approximately 1,000 word families. She argues, however, that cognates should still not be excluded from L2 vocabulary tests because their presence is crucial for obtaining an accurate estimate of vocabulary size.…”
Section: Cognates and Cognate Facilitationmentioning
confidence: 96%
“…Working with intermediate Russian learners of L2 English, Elgort (2013) found an effect of cognate facilitation on Vocabulary Size Test scores (Nation, 2006;Nation & Beglar, 2007). Elgort's participants' responses were more accurate for cognates than for non-cognates regardless of whether the test was administered in the original monolingual version or in a newly-designed bilingual version (with the multiple-choice options presented in Russian).…”
Section: Cognates and Cognate Facilitationmentioning
confidence: 99%
“…This test was first reported on in Nation & Beglar (2007) and is now supported by a growing body of research (Beglar 2010;Nguyen & Nation 2011;Elgort 2013). Beglar's (2010) examination of the 140-item monolingual VST in Japan with a mixture of native and non-native speakers showed that it had many features that typify a good test.…”
Section: The Vocabulary Size Testmentioning
confidence: 77%
“…Shortly afterward, bilingual versions of the VST were developed and began to gain momentum, in addition to the original monolingual version of the test. The bilingual versions of the VST, in which the multiple-choice options of the items are in the native language of the test takers, have been developed for different languages including Japanese, Korean, Vietnamese, Mandarin, Russian, and Persian (see Elgort, 2013;Karami, 2012;Nguyen & Nation, 2011;Stewart, 2009;Zhao & Ji, 2016). All these three measures of written receptive vocabulary size have been widely used in L2 vocabulary research.…”
Section: Research-article20182018mentioning
confidence: 99%
“…The VLT and VST have been identified as valid and reliable measures of vocabulary size (Akbarian, 2008;Beglar, 2010;Nation & Beglar, 2007;Schmitt et al, 2001;Xing & Fulcher, 2007). In addition, bilingual versions of both VLT and VST have been developed and recommended as appropriate alternatives to the monolingual versions (Elgort, 2013;Karami, 2012;Nation, 2007;Nguyen & Nation, 2011;Stewart, 2009;Zhao & Ji, 2016). Read (2013) reviewed the studies on development and validation of L2 vocabulary measures and reported that Schmitt et al (2001) conducted a comprehensive validation research to revise the VLT, previously developed by Nation (1983), and validated the new version with "over 800 learners in five different countries" (p. 48).…”
Section: The Right Measure Of Vocabulary Sizementioning
confidence: 99%